Cognitive and Lingrapromatic Significance of the Verb of Vision Perception in English and Uzbek Languages - Karabaeva, Barno (International Journal of Psychosocial Rehabilitation, 2020)
The article illustrates the lexemes of the microfield of visual perception: analyzes extralinguistic information explaining the mechanisms inclusion of some tokens in the composition of this microfield; more carefully used verbs of visual perception are followed, which were distributed over to the anonymous series, on the basis of the ternary opposition of the meanings in Uzbek and English.